Association of the apolipoprotein E ε4 allele in a Serbian population with Alzheimer’s dementia - Bašić, Jelena; Milošević, Vuk; Đorđević, Branka; Stefanović, Nikola; Cvetković, Marija; Jevtović Stoimenov, Tatjana; Stojanović, Ivana (Archives of Biological Sciences, 2023)
Paper description: Single nucleotide polymorphisms rs429358 and rs7412 in the apolipoprotein E gene (APOE) are of great importance for APOEε2/ε3/ε4 carrier status determination. APOEε2/ε3/ε4 allele carrier status in Alzheimer’s disease (AD) dementia and cognitively unimpaired subjects and the association of the APOEε4 allele with AD dementia risk in a Serbian population was assessed. The APOEε4 allele was found to be associated with a higher risk of AD dementia compared to the reference ε3 allele. This research is a potential contribution to improving diagnostic protocols for diagnosing and treating AD dementia in Serbia. Abstract: Although single nucleotide polymorphisms rs429358 and rs7412 in the apolipoprotein E gene (APOE) are widely investigated to analyze APOE alleles, there are no data on their association with Alzheimer’s disease (AD) dementia in a Serbian population. This study aimed to investigate the distribution of APOE ε2/ε3/ε4 alleles in patients with dementia due to AD and cognitively unimpaired subjects and to assess the association of the APOE ε4 allele with disease risk in the Serbian population. A case-control study included patients with dementia due to AD and cognitively unimpaired individuals. APOE rs429358 and rs7412 were analyzed using the Real-Time PCR method with allele-specific TaqMan assays, followed by APOE ε2/ε3/ε4 allele carrier status analysis. Patients had a significantly higher frequency of the APOE ε4 allele than the control group (P<0.001). The APOE ε4 allele was found to be associated with a 3-fold higher risk of AD dementia compared to the reference ε3 allele (P<0.001). In conclusion, this is the first study to suggest that carriers of the APOE ε4 allele have a higher risk of developing dementia due to AD than those who carry the APOE ε3 allele in the Serbian population.